Common Hematological Disorders Causing Pancytopenia and Importance of Bone Marrow Examination - Riaz Ahmed Qazi, Aijaz Ahmed Memon, Bharat Lai, Ameer Abbas Ali, „laved Husain Memon (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2016)
To evaluate the frequencies of common hematological disorders leading to Pancytopenia. We highlight the importance of bone marrow examination among the pancytopenic patients to rule out causes or diagnosis of conmion hematological disorders. Study Design: Observational study. Place & Duration: Diagnostic and Research Laboratory, Pathology Department, Peoples University of Medical & Health Sciences, Shaheed BanazeedAbad from June 2013 to June 2014. Material and Methods: Total 91 patients, 67 males and 24 females with their ages ranging from 5-59 years were included in this study. These patients were coming from rural and urban areas of district: (SBA), Sanghar and Naushahroferoze referred by different physicians for the laboratory diagnosis of pancytopenia. The diagnosis of pancytopenia was made by detailed history, clinicohematological findings and blood examination, bone marrow biopsy samples of these patients were taken and sent to the D&R lab in pathology department for the diagnosis of pancytopenia. Results: The mean age was 37+32 years and male to female ratio 1.6:1 were detected in our study. The frequency of megaloblastic anemia was 46.16% followed by aplastic anemia 30.76°A, acute myeloid leukemia 17.58% and acute lymphoblastic leukemia 5.5% among the total 91 pancytopenic patients. Conclusion: The frequency of megaloblastic anemia was higher among the patients with pancytopenia followed by aplastic anemia, acute myeloid leukemia, and acute lymphoblast leukemia required prevention and treatment of these disorders that causes pancytopenia by the reliable diagnostic method such as bone marrow examination,